Pädagogische Qualität als Thema der Trainerbildung - hat die Sportpädagogik Trainern Relevantes zu bieten? - Richartz, A.; Anders, D. (Leipziger Sportwissenschaftliche Beiträge, 2016)
Knowledge transfer from sport sciences to coaches` practice and coach education has received critical evaluation with sport pedagogy particularly affected. In a coach education project pedagogical content was focused on effective teaching/coaching. Scientific knowledge transfer was based on an observational quality research instrument. Coaches` attention was directed to behavioral quality markers using video-clips. Some 300 participants assessed pedagogical issues highly relevant for training routines, evaluated their pedagogical competencies worth improving and expected support for subsequent learning from an online learning platform. Learning environments in coach education should be designed more strictly to fit coaches` learning perspectives.